Multisectoral prioritization of zoonotic diseases in Uganda, 2017: A One Health perspective - Sekamatte, Musa (PLoS One, 2018)
BACKGROUND: Zoonotic diseases continue to be a public health burden globally. Uganda is especially vulnerable due to its location, biodiversity, and population. Given these concerns, the Ugandan government in collaboration with the Global Health Security Agenda conducted a One Health Zoonotic Disease Prioritization Workshop to identify zoonotic diseases of greatest national concern to the Ugandan government. MATERIALS AND METHODS: The One Health Zoonotic Disease Prioritization tool, a semi-quantitative tool developed by the U.S. Centers for Disease Control and Prevention, was used for the prioritization of zoonoses. Workshop participants included voting members and observers representing multiple government and non-governmental sectors. During the workshop, criteria for prioritization were selected, and questions and weights relevant to each criterion were determined. We used a decision tree to provide a ranked list of zoonoses. Participants then established next steps for multisectoral engagement for the prioritized zoonoses. A sensitivity analysis demonstrated how criteria weights impacted disease prioritization. RESULTS: Forty-eight zoonoses were considered during the workshop. Criteria selected to prioritize zoonotic diseases were (1) severity of disease in humans in Uganda, (2) availability of effective control strategies, (3) potential to cause an epidemic or pandemic in humans or animals, (4) social and economic impacts, and (5) bioterrorism potential. Seven zoonotic diseases were identified as priorities for Uganda: anthrax, zoonotic influenza viruses, viral hemorrhagic fevers, brucellosis, African trypanosomiasis, plague, and rabies. Sensitivity analysis did not indicate significant changes in zoonotic disease prioritization based on criteria weights. DISCUSSION: One Health approaches and multisectoral collaborations are crucial to the surveillance, prevention, and control strategies for zoonotic diseases. Uganda used such an approach to identify zoonoses of national concern. Identifying these priority diseases enables Uganda’s National One Health Platform and Zoonotic Disease Coordination Office to address these zoonoses in the future with a targeted allocation of resources.